2015
DOI: 10.1038/onc.2015.351
|View full text |Cite
|
Sign up to set email alerts
|

SLUG is required for SOX9 stabilization and functions to promote cancer stem cells and metastasis in human lung carcinoma

Abstract: Cancer stem cells (CSCs) are a promising target for cancer therapy, particularly for metastatic lung cancers, but how CSCs are regulated is largely unknown. We identify two proteins, SLUG (encoded by SNAI2 gene) and SOX9, that are associated with advanced stage lung cancers and are implicated in the regulation of CSCs. Inhibition of either SLUG or SOX9 sufficiently inhibits CSCs in human lung cancer cells and attenuates experimental lung metastasis in a xenograft mouse model. Correlation between SLUG and SOX9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 49 publications
13
90
0
Order By: Relevance
“…Similarly, we observed increased cell migration and invasion in Slug-overexpressing cells (Figure 5B,C). Tumor sphere formation, which is a key feature of malignant transformation and has been shown to be induced by Slug in human lung carcinoma, 20 also increased in Slug-overexpressing cells, as indicated by the increased number of large floating spheres under nonadherent and serum-starved conditions (Figure 5D,E). Together, these findings support the role of Slug in SWCNT-induced EMT activation and malignant transformation of human lung epithelial cells.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, we observed increased cell migration and invasion in Slug-overexpressing cells (Figure 5B,C). Tumor sphere formation, which is a key feature of malignant transformation and has been shown to be induced by Slug in human lung carcinoma, 20 also increased in Slug-overexpressing cells, as indicated by the increased number of large floating spheres under nonadherent and serum-starved conditions (Figure 5D,E). Together, these findings support the role of Slug in SWCNT-induced EMT activation and malignant transformation of human lung epithelial cells.…”
Section: Resultsmentioning
confidence: 85%
“…1719 Our previous studies have shown that Slug is highly expressed in lung CSCs and functions to promote metastasis in human lung carcinoma. 20 The main objective of this study was to determine whether Slug expression is upregulated in CNT-exposed lung cells and whether it plays a role in CNT-induced EMT activation and carcinogenesis. Here, we applied our previously developed chronic exposure model in which nontumorigenic human lung epithelial BEAS-2B (B2B) cells were continuously exposed to a low dose of SWCNT in culture over a prolonged period.…”
Section: Introductionmentioning
confidence: 99%
“…Slug has been shown to stimulate the expression of ZEB1 (38), a finding that is consistent with our data, and the increase in ZEB1 was indeed due to an increase in slug expression as a knockdown of slug in 14-3-3 Ϫ/Ϫ cells results in a decrease in ZEB1 protein levels. Slug expression has been positively associated with cancer progression, invasion, and metastasis without a parallel increase in snail, which suggests that snail and slug have different functions in tumor progression (95)(96)(97). Slug expression can be regulated by multiple transcription factors such as Myb, c-Jun (52,98), growth factors such as EGF (99) and TGF-␤ (100), and signaling pathways like the MAPK pathway (46,101).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of SNAI1 has similarly been linked with acquisition of CSC markers and functionality in a variety of tumours, including ovarian [Kurrey et al, 2009], colorectal [Fan et al, 2012], and pancreatic tumours . Likewise, SNAI2 has been reported to induce a CSC phenotype in MCF10A, a human mammary epithelial cell line [Bhat-Nakshatri et al, 2010], and knockdown of SNAI2 in non-small cell lung cancer cells reduced their tumour sphere-forming ability in vitro and metastatic tumour potential and tumour growth in vivo [Luanpitpong et al, 2016].…”
Section: Regulation Of Snail Family Expression and Functionmentioning
confidence: 99%